Efficacy of Seed Treatment by Fungicides and Neem Products for Controlling Seed and Seedling Rot of Blackgram - K.C. SAHU; A.K. KAR (Seed Research, 2026)
Fusarium moniliforme, a potential seed borne pathogen, was isolated from farmer’s seed samples of black gram. Infected seeds of var. Sarala were treated with neem leaf extract, neem seed extract, neem oilcake extract, Neemazal (commercial formulation), fungicides; Bavistin and Vitavax, separately. The treated seeds were stored in cloth bags as well as polythene bags. Samples were drawn at bimonthly intervals and observations on germination and seed moisture content were taken. The per cent association of the fungi from the seeds and incidence of seed rot were also studied. All the treatments reduced infection of Fusarium moniliforme, improved germination and reduced incidence of seed and seedling rot. Both fungicides were superior to neem products in reduction of seed infection and incidence. Among neem products Neemazal (0.3%) and neem oil (0.3%) were significantly superior. Seed infection and seed moisture content were influenced by atmospheric moisture and temperature. Seeds stored in polythene bags were better than cloth bags.